The benefits, challenges and implications for integrating emerging technologies in risk evaluation procedures for supply chains in transportation logistics - Lord Emmanuel Yamoah; Ronald Osei Mensah; Agyemang Frimpong (Discover Sustainability)
Abstract This study examines the integration of emerging technologies into risk evaluation procedures for supply chains, specifically within the context of transportation logistics. As global supply chains become more complex, the role of innovative technologies such as artificial intelligence (AI), the Internet of Things (IoT), and blockchain is increasingly vital in improving risk management practices. The findings highlight the importance of these technologies in enhancing risk evaluation, with particular attention to their ability to address challenges such as inventory management and supplier disruptions. The research also reveals that, demographic factors including gender and educational background, influence perceptions of risk evaluation effectiveness. Scenario analysis emerged as the preferred method for evaluating risks, while face-to-face communication, such as meetings and presentations, remains the most common approach for disseminating information. The study underscores the need for supply chain professionals to embrace emerging technologies, not only for their potential to improve risk assessment processes but also for their capacity to foster more proactive and efficient risk management strategies. These insights are valuable for companies looking to strengthen their risk management frameworks and remain competitive in an increasingly technology-driven landscape.